2010
DOI: 10.3233/jad-2010-1312
|View full text |Cite
|
Sign up to set email alerts
|

Neuronutrition and Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a complex neurological disorder with several unequivocally identified genetic risk factors. Among the several environmental factors proposed for AD, dietary protective and risk factors have been most compelling. In particular, diets rich in saturated fatty acids and alcohol, and deficient in antioxidants and vitamins appear to promote the onset of the disease, while diets rich in unsaturated fatty acids, vitamins, antioxidants, and wine likely suppress its onset. Evidence suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 196 publications
(202 reference statements)
2
48
0
1
Order By: Relevance
“…Importantly, toxicity in C. elegans ND models is influenced by the insulin pathway [(8, 9, 16, 47) and our own unpublished observations] providing a link between food source and proteotoxicity. Although the differences between the nematode and human diet are obvious, our observation is consistent with an increasing number of studies that support a role of environmental factors, such as diet and environmental toxins, in ND (52,53,73).…”
supporting
confidence: 89%
“…Importantly, toxicity in C. elegans ND models is influenced by the insulin pathway [(8, 9, 16, 47) and our own unpublished observations] providing a link between food source and proteotoxicity. Although the differences between the nematode and human diet are obvious, our observation is consistent with an increasing number of studies that support a role of environmental factors, such as diet and environmental toxins, in ND (52,53,73).…”
supporting
confidence: 89%
“…Interestingly, there has been increasing support for diet playing a role in AD (4)(5)(6). A number of dietary factors such as saturated fatty acids, higher calorie intake, and excessive alcohol (7) have been reported to increase the risk of dementia and AD (8). In particular, a number of studies have shown the close association of alcoholic consumption and dementia, although the exact mechanisms are still not known (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Red wine contains at least 19 types of polyphenols; among these, resveratrol is the most abundant 13 . Thus, the beneficial effect of wine on neurodegeneration can be attributed to resveratrol 10 .…”
Section: Main Conclusionmentioning
confidence: 99%
“…Since then, it has been increasing exponentially, and it is now considered a 21 st century epidemic, affecting approximately 26 million people worldwide and one quarter of the people aged above 85 years [8][9][10][11] .…”
Section: Alzheimer's Disease: the Dimension Of The Problemmentioning
confidence: 99%
See 1 more Smart Citation